(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Population fluctuations and seasonal abundance of Hemiberlesia lataniae (Signoret), also of its parasite Habrolepis aspidioti Compere & Annecke, and of lcerya seychellarum (Westwood) on Morus alba were studied in Egypt (Giza governorate) during 1997-1998. Both Hemiberlesia lataniae and Habrolepis aspidioti had four population peaks during the year, while I. seychellarum had two peaks. Hemiberlesia lataniae was more abundant than I. seychellarum. The effects of climatic factors such as temperature, relative hurnidity, photoperiod, dew point and wind velocity are discussed.